2021
DOI: 10.1212/nxi.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute Autoantibodies as Biomarkers in Autoimmune Neurologic Diseases

Abstract: ObjectiveTo identify and characterize autoantibodies (Abs) as novel biomarkers for an autoimmune context in patients with central and peripheral neurologic diseases.MethodsTwo distinct approaches (immunoprecipitation/mass spectrometry–based proteomics and protein microarrays) and patients' sera and CSF were used. The specificity of the identified target was confirmed by cell-based assay (CBA) in 856 control samples.ResultsUsing the 2 methods as well as sera and CSF of patients with central and peripheral neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…Antibodies with rather non-conformational epitopes do not or not significantly lose their reactivity upon antigen linearization, such as the commercial anti-AGO1 antibody and a subgroup (here: subgroup-3) of AGO1 Abspositive patients. Using this approach, all 14 tested patients from our first study bound a conformational epitope, which confirms our first suspicion, where denatured (Western blot) or truncated (one spot of the protein arrays) AGO proteins were not or less useful to detect these antibodies (8).…”
Section: Of Disease Repartition Antibody Titers and Igg Subclasses Be...supporting
confidence: 74%
See 4 more Smart Citations
“…Antibodies with rather non-conformational epitopes do not or not significantly lose their reactivity upon antigen linearization, such as the commercial anti-AGO1 antibody and a subgroup (here: subgroup-3) of AGO1 Abspositive patients. Using this approach, all 14 tested patients from our first study bound a conformational epitope, which confirms our first suspicion, where denatured (Western blot) or truncated (one spot of the protein arrays) AGO proteins were not or less useful to detect these antibodies (8).…”
Section: Of Disease Repartition Antibody Titers and Igg Subclasses Be...supporting
confidence: 74%
“…As patient antibodies appear to predominantly bind the native AGO proteins, immunoprecipitation has initially been considered the only method to reliably detect anti-Su/Ago2 antibodies (9). Nevertheless, while we confirmed that denatured (Western blot) or truncated AGO proteins were not useful to detect these antibodies, our recently established CBA appeared reliable to detect the native antigen (8). Here, we established a sensitive ELISA approach which we applied to estimate the frequency of AGO1 in NP and AID and to determine sensitivity differences between AGO1 and AGO2 Abs.…”
Section: Of Disease Repartition Antibody Titers and Igg Subclasses Be...mentioning
confidence: 81%
See 3 more Smart Citations